Spider Diversity Pattern and Community Composition in the South Eastern Nigeria: An Analysis of Habitat Differences - C.D. Ezeonyejiaku; C.O. Okoye; M.C. Anaesoronye; T.C. Mogbo (Journal of Applied Sciences and Environmental Management)
Spider diversity plays an important role in the balance of nature. Thus, a study on the diversity of spiders was carried out in Awka, Anambra State in the South Eastern Nigeria from January, 2018 to June, 2018. Spiders were collected from three habitats which include: residential areas, farmlands and forest regions in the study area using handpicking and vegetative beating methods. A total of one hundred and twenty-five (125) spiders belonging to ten (10) families and comprising of thirteen (13) species were identified. Ninety-three (93) spiders were collected from residential areas, twenty-one (21) from farmlands and eleven (11) from forest regions. Results of the relative abundance of spider species in different habitat showed that Physocyclus globosus has the highest abundance of species having 71.2% with composition of eighty-nine (89) spiders. Residential areas recorded the highest abundance of spiders having 74.4% and species composition of ninety-three (93) spiders. Forest regions recorded the highest species diversity index (H) of 1.7202. The study revealed that spider diversity is influenced by the type of habitat, vegetation and environmental disturbances.